Advances in Metal-Organic Frameworks (MOFs) Based Flexible Sweat Sensors (Journal of Fiber Bioengineering and Informatics, 2024)
Metal-organic frameworks (MOFs) demonstrate great potential in biosensing applications, particularlyin sweat sensing, due to their high specific surface area, adjustable pore sizes, and unique catalyticproperties. This review presents the advancements, fabrication techniques and potential applicationsof flexible sweat sensors utilizing MOFs. The background and importance of MOFs in sweat sensingwere introduced, underscoring their capacity to elevate the efficiency and precision of such sensors.The structural optimisation, ligand choice, and fabrication techniques of MOFs were discussed. Varioussynthesis methods were explored, including electrochemical, solvothermal, room-temperature, andmicrowave/ultrasound-assisted approaches. The applications of MOF-based sweat sensors in traceelement detection, colourimetric sensing, sports monitoring, and biomedicine were highlighted. MOFs’high sensitivity, selectivity, and stability in these contexts underscore their potential to enhance sensorperformance. The review concludes by discussing the challenges faced by flexible sweat sensors based onMetal-Organic Frameworks (MOFs), such as the diversification of detectable substances. It outlinesfuture directions, particularly towards intelligence and high efficiency. It emphasizes the necessityof achieving high precision and multifunctionality. This review comprehensively analyses the currentstatus and future prospects of flexible sweat sensors utilising MOFs, highlighting their significant role inadvancing sweat-sensing technology.
Keywords: MOF; Sweat Sensors; Smart Wearables; Preparing Technology; Application.